4(n+6)=8-4(n-2)

Simple and best practice solution for 4(n+6)=8-4(n-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(n+6)=8-4(n-2) equation:


Simplifying
4(n + 6) = 8 + -4(n + -2)

Reorder the terms:
4(6 + n) = 8 + -4(n + -2)
(6 * 4 + n * 4) = 8 + -4(n + -2)
(24 + 4n) = 8 + -4(n + -2)

Reorder the terms:
24 + 4n = 8 + -4(-2 + n)
24 + 4n = 8 + (-2 * -4 + n * -4)
24 + 4n = 8 + (8 + -4n)

Combine like terms: 8 + 8 = 16
24 + 4n = 16 + -4n

Solving
24 + 4n = 16 + -4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4n' to each side of the equation.
24 + 4n + 4n = 16 + -4n + 4n

Combine like terms: 4n + 4n = 8n
24 + 8n = 16 + -4n + 4n

Combine like terms: -4n + 4n = 0
24 + 8n = 16 + 0
24 + 8n = 16

Add '-24' to each side of the equation.
24 + -24 + 8n = 16 + -24

Combine like terms: 24 + -24 = 0
0 + 8n = 16 + -24
8n = 16 + -24

Combine like terms: 16 + -24 = -8
8n = -8

Divide each side by '8'.
n = -1

Simplifying
n = -1

See similar equations:

| 12+p=8+7 | | =x^2+4x | | 2(cos(2pi))=0 | | 4m^5n^0(5m^3)= | | 2/7x234/1 | | 4(2x+-1)=.5(16x+-8) | | ln(3x-2)=2.3 | | 3xwhat=123 | | 12y+10y=20y-3 | | 3(n+8)=3-3(n-7) | | 12+9y=9 | | 17-5x=35 | | 3xa=123 | | 12y+10y=20y-60 | | 1/4x=17 | | 7(n+8)=2-5(n-6) | | 8x+1y=26 | | =3x^2-9x | | -15+31=-2(x+1) | | 2(5h)+25=40h | | -16z-0.7=-26z+2.1 | | 81a^2=4 | | 0=x^2-9x^4 | | 2ln(y)=y | | 5(3+8)=(X*3)+(X*8) | | 8r+9r=-21 | | (2x-8)-10=2-8x | | 9x+40=x-16 | | 5h(p)+25=20h(p) | | 3(n+7)=7-4(n-7) | | 8xsquared-47x-6=0 | | 2+8=33(2x) |

Equations solver categories